Nanoscale magnetic structure and properties of solution-derived self-assembled La0.7Sr0.3MnO3 islands - Zabaleta, J. (2012)
Strain-induced self-assembled La0:7Sr0:3MnO3 nanoislands of lateral size 50150 nm and height 1040 nm have been grown on yttria-stabilized zirconia (001)-substrates from ultradiluted chemical solutions based on metal propionates. The nanoislands grow highly relaxed withstanding the epitaxial relation ð001ÞLSMO ½110==ð001ÞYSZ ½010 and show bulk-like average magnetic properties in terms of Curie temperature and saturation magnetization. The interplay of the magnetocrystalline and shape anisotropy within the nanoisland ensemble results in an in-plane magnetic anisotropy with a magnetocrystalline constant K1ð150 KÞ ¼ ð561Þ kJ=m3 and in-plane easy axis along the ½110 La0:7Sr0:3MnO3 direction as measured, for the first time, through ferromagnetic resonance experiments. Magnetic force microscopy studies reveal the correlation between nanoisland size and its magnetic domain structure in agreement with micromagnetic simulations. In particular, we have established the required geometric conditions for single domain, multidomain, and vortex configurations.